Microbiomics and volatile metabolomics-based investigation of changes in quality and flavor of oat (Avena sativa L.) silage at different stages - Deng, Xiaochen; Jia, Yushan; Ge, Gentu; Wang, Zhijun; Liu, Mingjian; Bao, Jian; Zhao, Muqier; Si, Qiang; Liu, Yichao; Zhao, Weixuan (Frontiers in Plant Science, 2023)
This study aimed to analyze the fermentation quality, microbial community, and volatile metabolites of oat silage harvested at two different stages, while examining the correlation between microorganisms and volatile metabolites. Oats were harvested at two growth stages (pre-heading [PRH] and post-heading [POH] stages), followed by 90 days of natural fermentation, with 6 replicates per treatment. Pre-and post-silage samples were randomly selected for nutrient composition, fermentation parameters, microbial population, and high-throughput sequencing analysis. Volatile metabolomics analysis was also performed on samples after 90 days of fermentation to detect differences in flavor quality after silage. The effect of growth stage on the nutrient content of oats was significant, with preheading oats having higher crude protein and post-heading oats having higher water soluble carbohydrates content (p < 0.05). Following a 90-day fermentation period, the pH and ammonia nitrogen/ total nitrogen levels in the PRH-90 (silage from pre-heading oats after 90 days of fermentation) group demonstrated a significant decrease (p < 0.05), whereas the lactic acid content was notably higher compared to the POH-90 (silage from post-heading oats after 90 days of fermentation) group (p < 0.05). Lactiplantibacillus dominated in the PRH-90 group and Enterococcus dominated in the POH-90 group, with abundances of (> 86%) and (> 87%), respectively. The differential volatile metabolites of the two treatment groups were dominated by esters and terpenoids, and the differences in flavor were mainly concentrated in sweet, green, and fruity odors. The results of kyoto encyclopedia of genes and genomes pathway enrichment analysis demonstrated three major metabolic pathways: phenylpropanoid biosynthesis, phenylalanine metabolism, and biosynthesis of secondary metabolites. Specific microorganisms were significantly correlated with flavor indicators and flavor metabolites. Lactiplantibacillus was significantly positively correlated with flavor substances indicating sweet and fruity flavors, contributing to good flavor, while Enterococcus was significantly and positively correlated with flavor substances indicating bad flavors. In summary, growth stage had significant effects on nutritional components, fermentation parameters and flavor quality of oats, with the